2016
DOI: 10.1089/thy.2016.0141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thyroid Function Variations Within the Laboratory Reference Range on Health Status, Mood, and Cognition in Levothyroxine-Treated Subjects

Abstract: Background: There has been recent debate within the thyroid field regarding whether current upper limits of the thyrotropin (TSH) reference range should be lowered. This debate can be better informed by investigation of whether variations in thyroid function within the reference range have clinical effects. One important target organ for thyroid hormone is the brain, but little is known about variations in neurocognitive measures within the reference range for thyroid function.Methods: This was a cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…In relation to coronary heart disease Åsvold et al [16] (n = 55,412) have observed that lowering the upper TSH reference value did not show any association with events of coronary heart disease. A similar observation has been made by Samuels et al [17] (n = 132) in relation to health status, cognition and mood. Walsh et al [18] evaluated whether changing the dose of thyroxine treatment can have an effect on well-being.…”
Section: Clinical Studies Dealing With Reference Levels For Tsh For Asupporting
confidence: 87%
“…In relation to coronary heart disease Åsvold et al [16] (n = 55,412) have observed that lowering the upper TSH reference value did not show any association with events of coronary heart disease. A similar observation has been made by Samuels et al [17] (n = 132) in relation to health status, cognition and mood. Walsh et al [18] evaluated whether changing the dose of thyroxine treatment can have an effect on well-being.…”
Section: Clinical Studies Dealing With Reference Levels For Tsh For Asupporting
confidence: 87%
“…where the random variables Z and v 2 in equation (5) are the same as those in equation (4). The R package tolerance 24,25 can be used to compute c 5 .…”
Section: Tolerance Intervalsmentioning
confidence: 99%
“…For example, underestimating the upper limit of a reference range would mean classifying a large number of people as diseased, thus affecting the doses of medication prescribed. 4 Construction of appropriate reference ranges is therefore crucial in laboratory medicine practice. Well-known general references 3 , 5 – 9 and a case for teaching tolerance intervals in introductory statistics courses 10 are available.…”
Section: Introductionmentioning
confidence: 99%
“…patients remain symptomatic despite having normal thyroid hormone levels. Similar to the opinion of Kopp, Mary H. Samuels recently stated the following: “It is a common clinical observation that some otherwise healthy patients with hypothyroidism continue to complain of fatigue, poor mood, inability to concentrate, and vague cognitive difficulties (often described as “brain fog”) despite normal TSH levels” [67] . Similar comments have been made by other authors in the past [68] , [69] .…”
Section: How Effective Is Thyroxine Treatment? Also Known As Resolvinmentioning
confidence: 85%